Hospital priority setting in a mixed public/private health system: a case study of a chilean hospital - Valdebenito, Carolina; Kapiriri, Lydia; Martin, Douglas K. (Acta Bioethica, 2009)
The purpose of this study was to describe, using qualitative case study methods, and evaluate, using the ethical framework 'accountability for reasonableness', priority setting in a hospital in Chile. In policy making contexts that have historically been dominated by central authority, especially where there are limited resources, fair priority setting processes can empower people, foster social learning, improve the quality of the decisions, enhance compliance with policy decisions, and increase public confidence in the hospital.